FAMILY SUPPORTIVE GROUP INTERVENTIONS FOR SCHIZOPHRENIA PATIENTS AT RSJD DR SAMSI JACOBALIS - Alyasa, M Hafidh; Yuningsih, Yuyun (Indonesian Journal of Social Work, 2025)
This research study entitled "Family Support for People with Mental Disorders (Schizophrenia) Through the Family Supportive Group Program at RSJD Dr. Samsi Jacobalis, Bangka Belitung Islands Province" aims to explain how family support for people with mental disorders is given by the family for the recovery of people with mental disorders and to restore their functioning through the family supportive group program. The method used is qualitative descriptive with a case study approach. In selecting informants using purposive sampling techniques, and data collection techniques using observation, interviews, and documentation studies. The results of the study explain that family support for people with mental disorders through the Family Supportive Group Program at RSJD Dr. Jacobalis, Bangka Belitung Islands Province has a very important role in providing family support for individuals with mental disorders, especially schizophrenia. Through a holistic approach, this program has succeeded in providing emotional, informational, real, and hopeful support to families, which are greatly needed in the journey of treatment and recovery of family members affected by mental disorders. Thus, the Family Supportive Group Program not only helps improve the well-being of individuals with mental disorders, but also strengthens family relationships and builds an inclusive community in facing mental health challenges.